Evaluating the Impact of Technological Infrastructure on Teaching, Learning, and Institutional Effectiveness in Technology Education Institutions - Gladys Jean A Bandol; Maiko Rosed M Trojillo; Emilie S Estelloso (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: The study evaluates the integration of technological infrastructure in schools, highlighting its positive impact on engagement, accessibility, and administration. Despite benefits like efficiency and improved communication, challenges remain in network connectivity, support, and the digital divide. Findings aim to inform policy for more effective, equitable technology use in education. Methodology: The study uses a quantitative descriptive design to assess technological infrastructure integration in a rural elementary school. Complete enumeration of faculty and staff ensures accurate data. A validated self-made survey measures technology's impact on engagement, access, teaching efficiency, and performance. Descriptive statistics, including mean and standard deviation, analyze trends and the extent of technology's educational influence. Main Findings: The study found high technological integration in elementary schools, with hardware availability scoring highest, reflecting strong institutional support. However, technical support services scored lowest, indicating a need for better troubleshooting assistance. Technology significantly enhanced student engagement but had a moderate impact on academic performance. Literature supports these findings, emphasizing that while digital tools boost interaction, improving outcomes requires strong technical support and teacher training. Mateo Elementary School should invest in both areas to maximize the effectiveness of its technological infrastructure. Novelty/Originality of this study: The study advances existing knowledge by providing a holistic evaluation of technological infrastructure in elementary schools, focusing on both hardware/software integration and often-overlooked aspects like technical support and network connectivity. It highlights the disparity between high engagement and moderate performance gains, emphasizing the need for teacher training and equitable access. The findings offer actionable insights for policymakers and educators to optimize technology's role in education.